1973
DOI: 10.1161/01.res.33.4.412
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Activation of Cardiac Glycogen Phosphorylase in Ischemia and Anoxia

Abstract: The effects of ischemia and anoxia on cardiac adenosine 3',5'-monophosphate (cyclic AMP) concentration, glycogen phosphorylase activity ratio (-5'-AMP: + 5'-AMP), phosphorylase kinase activity ratio (pH 6.8:8.2), and myocardial contractility (left ventricular dP/dt) were studied in an open-chest rat heart preparation. Ischemia produced by termination of coronary blood flow increased cyclic AMP from 0.55 to 0.77 yu.moles/kg in 5 seconds and phosphorylase from 0.14 to 0.57 in 20 seconds. Anoxia induced by breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
36
0

Year Published

1975
1975
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(38 citation statements)
references
References 28 publications
(23 reference statements)
2
36
0
Order By: Relevance
“…This was responsible for a consistently higher 4 This seems to be largely caused by the conversion of phosphorylase from the b to the a form, which could be mediated by epinephrine through an increased production of cyclic AMP. 16 Increased glycogen synthesis in the myocardium has been reported in experimental animals after exercise. 17 FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…This was responsible for a consistently higher 4 This seems to be largely caused by the conversion of phosphorylase from the b to the a form, which could be mediated by epinephrine through an increased production of cyclic AMP. 16 Increased glycogen synthesis in the myocardium has been reported in experimental animals after exercise. 17 FIGURE 5.…”
Section: Discussionmentioning
confidence: 99%
“…The role of coronary blood flow in maintaining a suitable intracellular environment in addition to providing the oxygen supply has been emphasized recently in studies comparing the effects of anoxia with those of ischemia (15)(16)(17). Ischemia has been shown to be more detrimental to cellular function and metabolism than is anoxia in which coronary blood flow is maintained at normal rates.…”
mentioning
confidence: 99%
“…Although the present model most closely resembles hypoxic ischemia, GP kinase may have been activated if 1 h of ischemia induced anoxia. Though the present study did not determine whether GP in the microsomel fraction was GP-a or -b, but it is likely that the majority of GP in the present study was GP-b, since hypoxic ischemia increases GP-a [23,34] that could be liberated from SR [17]. In addition, reperfusion increased GP-b for long periods after ischemia [9].…”
Section: Discussionmentioning
confidence: 61%
“…On the other hand, Morgan and Parmeggiani concluded that phosphofructokinase activated GP-b in the anaerobically reperfused isolated heart [3] . In contrast, no change in GP activity was reported in the anoxic heart [28,34] , and GP kinase was reported to be activated by Mg2+ and Ca2+ [34] . Although the present model most closely resembles hypoxic ischemia, GP kinase may have been activated if 1 h of ischemia induced anoxia.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation